Enhancing Quranic Reading Skills through the Jibril Method: A Case Study in Non-Formal Islamic Education - Putra, Gilang Darma; Safarudin, Rizal; Zulfamanna, Zulfamanna (STIT Ahlussunnah Bukittinggi, 2026)
The ability to recite the Quran with proper pronunciation in accordance with the rules of tajweed is a fundamental competency in Islamic education. However, many students have not yet mastered it to the fullest extent. This study aims to examine the effectiveness of the Jibril method on students’ ability to recite the Quran. This study employs a qualitative approach with a case study design to explore the application of the Jibril method within the context of non-formal Islamic education. Data were collected through observation, interviews, and documentation involving educators, institutional administrators, and students, and were subsequently analyzed through data reduction, data presentation, and drawing conclusions. The results indicate that the Jibril method significantly improves reading fluency, accuracy of articulation points, and mastery of tajweed. Furthermore, this method also enhances students’ learning motivation, discipline, and active engagement. These findings indicate that the Jibril method is an effective learning strategy for improving Quranic reading skills in non-formal Islamic education; however, its optimal and sustainable implementation requires support from educators’ competencies and systematic learning management.